2017
DOI: 10.1161/circheartfailure.115.002637
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Presentation and Outcomes Between Children With Familial Dilated Cardiomyopathy and Children With Idiopathic Dilated Cardiomyopathy

Abstract: Background Research comparing the survival of children with familial dilated cardiomyopathy (FDCM) to that of children with idiopathic dilated cardiomyopathy (IDCM) has produced conflicting results. Methods and Results We analyzed data from children with FDCM or IDCM using the National Heart, Lung, and Blood Institute-funded Pediatric Cardiomyopathy Registry. Compared to children with IDCM (n=647), children with FDCM (n=223) were older (mean 6.2 vs. 4.5 years, P <0.001), less often had heart failure (64% vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 29 publications
1
16
3
4
Order By: Relevance
“…Our results support the evidence that children with a hereditary cardiomyopathy who present in acute heart failure tend to have poorer outcomes compared to patients with idiopathic cardiomyopathy. 12 Of note, our study and previous research have not compared mutation-negative, familial cases compared to mutation-positive cases, and this would be of interest for further study. Furthermore, identifying patients who have genetic syndromes allows the health care team to provide appropriate anticipatory guidance to the family and appropriate medical care for the additional sequela that may develop.…”
Section: Discussionmentioning
confidence: 89%
“…Our results support the evidence that children with a hereditary cardiomyopathy who present in acute heart failure tend to have poorer outcomes compared to patients with idiopathic cardiomyopathy. 12 Of note, our study and previous research have not compared mutation-negative, familial cases compared to mutation-positive cases, and this would be of interest for further study. Furthermore, identifying patients who have genetic syndromes allows the health care team to provide appropriate anticipatory guidance to the family and appropriate medical care for the additional sequela that may develop.…”
Section: Discussionmentioning
confidence: 89%
“…Recent data indicate that in the pediatric population there is no survival difference between familial DCM and idiopathic DCM after adjustment for other factors. (18) However, the majority of patients in this study did not undergo genetic testing and therefore it is unclear whether there might be a survival difference based on genotype. Overall, older age, heart failure, and greater left ventricular dilation at diagnosis were independently associated with increased risk of the combined endpoint of transplantation and death.…”
Section: Isolated Non-syndromic Cardiomyopathymentioning
confidence: 87%
“…3 The Pediatric Cardiomyopathy Registry found that 1-year survival was significantly better in patients with familial dilated cardiomyopathy (87%) compared with idiopathic dilated cardiomyopathy (60%). 18 In addition, patients with familial isolated cardiomyopathy had higher left ventricular ejection fractions, lower end-diastolic and end-systolic dimensions, and lower left ventricular mass than those with idiopathic dilated cardiomyopathy. Left ventricular end-diastolic dimension z-scores predicted an increased risk of death or transplantation in children with familial isolated cardiomyopathy.…”
Section: Cause Of Dcmmentioning
confidence: 97%